Bringing classes back into poverty discussions - Özgün, Gizem; Dolcerocca, Antoine (Frontiers in Sociology, 2023)
The 1980s saw a shift in the emphasis of discourse on poverty from production relations to consumption relations, with levels of consumption and purchasing power used to define poverty. Based on this concept, much of the research establishes absolute poverty lines or develops relative indicators to distinguish between "poor" and "non-poor". This paper makes the case that such poverty measurement, while useful for assessing trends over the long term or taking into account relative dynamics, distorts our knowledge of poverty by hiding its root causes and results in overly optimistic interpretations. These discussions also decontextualize poverty from its political and economic context by uncritically accepting and promoting neoliberal regime. Moreover, the article questions the meaning of the “eradication of poverty” and suggests that the nominal rise in PPP income obscures historical capitalist accumulation processes (such as dispossession, proletarianization and depeasantization). As a result, the study suggests to recenter the analysis on the material causes of poverty, which are rooted in the functioning of the capitalist system, its antagonistic character, and the class-based contradictions of production itself.